2014
DOI: 10.1111/cge.12404
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic heterogeneity and mutational spectrum in a cohort of 45 Italian males subjects with X‐linked ectodermal dysplasia

Abstract: Ectodermal dysplasias (EDs) are a group of genetic disorders characterized by the abnormal development of the ectodermal-derived structures. X-linked hypohidrotic ectodermal dysplasia, resulting from mutations in ED1 gene, is the most common form. The main purpose of this study was to characterize the phenotype spectrum in 45 males harboring ED1 mutations. The study showed that in addition to the involvement of the major ectodermal tissues, the majority of patients also have alterations of several minor ectode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 22 publications
1
15
0
4
Order By: Relevance
“…The EDA gene was first cloned in 1996 and encodes a TNF‐related ligand family type II trimer transmembrane protein which participates in intercellular signal communication during the process of ectodermal organ development . To this day, about 300 species of EDA gene mutations have been reported, including EDA gene point mutation as well as splice site mutation, insertion or deletion, chromosomal changes, and so on . In clinical practice, Sanger sequencing is usually used in gene test of XLHED because the length of EDA gene is short.…”
Section: Discussionmentioning
confidence: 99%
“…The EDA gene was first cloned in 1996 and encodes a TNF‐related ligand family type II trimer transmembrane protein which participates in intercellular signal communication during the process of ectodermal organ development . To this day, about 300 species of EDA gene mutations have been reported, including EDA gene point mutation as well as splice site mutation, insertion or deletion, chromosomal changes, and so on . In clinical practice, Sanger sequencing is usually used in gene test of XLHED because the length of EDA gene is short.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent cohort of 133 Italian ED individuals, pathogenic changes were identified in 106 subjects (80%). EDA , WNT10A , EDAR , and EDARADD variants were detected as 45, 25, 7.5, and 1.5%, respectively [Guazzarotti et al, 2015]. In another large cohort study, 124 European HED patients were investigated by Sanger sequencing and MLPA analyses of EDA , EDAR , EDARADD , TRAF6 , and EDA2R , revealing pathogenic changes in 101 out of 124 HED individuals (81.5%).…”
Section: Edaraddmentioning
confidence: 98%
“…Guazzarotti et al reported that dental agenesis, sweating impairment, and hair alteration were found in 97.5%, 86.7%, and 93.3% of the patients with XLHED, respectively. In this article, patient ED44 particularly featured only dental abnormality among the triad of HED symptoms, and patient ED8 featured only sweating deficiency as the major clinical sign (Guazzarotti et al , ). In another study, there were three patients with XLHED (patients EDA1‐F14, EDA1‐F16, and EDA1‐F21) that had abnormalities in teeth and hair but not in sweat glands (Cluzeau et al , ).…”
Section: Introductionmentioning
confidence: 91%